KEBIJAKAN PEMERINTAH DALAM UPAYA MELESTARIKAN NILAI-NILAI PANCASILA DI ERA REFORMASI - Jantje Tjiptabudy (Faculty of Law, Universitas Pattimura, 2010)
Pancasila is the philosophy, the Indonesian state ideology, which means that the Pancasila as a source of inspiration and source of solutions to the nation's problems. In a development in the reform era of pure values contained in Pancasila termaknai not in the life of nation and state. This is what lies behind the author to see how government policies in an effort to preserve the values of Pancasila in the reform era. The results obtained that the translation of Pancasila, which can be used as guidance in the life of nation and state are necessary in the current reform era. Pancasila seems to have been completely forgotten by the various groups in society, although formally. Therefore the government should act in accordance with the values of Pancasila itself Every precepts of Pancasila should be internalized and implemented, government policies should be in accordance with the application of the principles of Pancasila. Does the government have to be firm and fast in ensuring its citizens carry out this first principle of religious life in peace without any confusion in the run his religion from interference deviant teachings, whether the government has made regulations in which the moral attitude of humanity based on the absence of interest groups , whether the government has been able to overcome all understand class, ethnicity, tribe, race, religion or class of individuals that can not be sharpened into conflict and hostility, but it makes a difference who becomes a force for unity of this nation, whether the people led by the wise men in making decisions together unutuk public interest. And lastly whether the government is providing justice for every citizen in the form of welfare, security, assistance, subsidies, and a chance to live without any distinction of rights.